Analisis Yuridis Penyelesaian Wanprestasi Dalam Perjanjian Kerjasama Usaha Jasa Jaringan Internet Berlangganan Aidea Guntur Net Di Kab. Indragiri Hilir - Narita Nasution; Ali Azhar; Vivi Arfiani Siregar (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2026)
The business cooperation agreement for Aidea Guntur Net's subscription internet network service in Indragiri Hilir Regency has frequently encountered problems of default (wanprestasi) in its implementation, both in the form of delayed payments by subscribers and discrepancies in the quality of services provided, resulting in losses to the aggrieved party. This research aims to identify and analyze the forms of default and the resolution efforts undertaken in the cooperation agreement, with the following problem formulations: (1) what forms of default occur, and (2) how the resolution efforts for default are carried out by the parties. This research employs a sociological (empirical) legal research method with a qualitative approach, using primary data obtained through interviews and secondary data from literature study, which were then analyzed descriptively and qualitatively. The results indicate that default occurs in the form of delayed payments and discrepancies in service quality, and its resolution is predominantly carried out through non-litigation channels, namely deliberation and negotiation between the parties, considered more effective, efficient, and able to maintain good relations, while litigation has never been pursued in resolving such disputes.